Framing strategic news from the perspective of media organizations in Malaysia - Azahar Kasim,; Adibah Ismail,; Sazali Abd Wahab, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Strategic news is published news with an implied agenda without explaining the truth. Nowadays, most media are more comfortable playing tug of war in their writing than telling the truth because of the news framing process. The process of generating strategic news is done by journalists and editors of a media organization by conducting the franchise process first to enable them to reach the target audience. Framing news is the cause for the reader's shift of understanding of news framed by the newspaper until the community's perception has been successfully changed. This study utilizes a qualitative method; three personality and media experts were interviewed to obtain relevant data regarding media agenda, framing and strategic news. The informants were from media conglomerates in Malaysia – Media Prima, Bernama TV and former Berita Harian Group Editor-in-Chief. The exploration of media practioner perspectives on news writing and framing allowed the researcher to delve into fundamental questions in journalism, specifically in the fragment of journalism ethics. The findings show that the framing of an issue was both deliberate and unintentional. Strategic news is the result of the interconnections between media agenda, ethics and journalism, editor responsibility and news framing, and manipulation by the media to advocate the success of the government’s mission and vision.